1995
DOI: 10.1288/00005537-199510000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Complications of endoscopic sinus surgery in a residency training program

Abstract: Endoscopic sinus surgery (ESS) is now taught in most otolaryngology residency programs in the United States. However, this is technically challenging surgery and concerns exist regarding patient safety early in the surgeon's learning curve. The authors reviewed 193 cases of ESS performed by residents, under faculty supervision at our program, between 1987 and 1992. Sixty-seven percent of patients underwent bilateral anterior ethmoidectomy, 40% had bilateral total ethmoidectomy, and 44% had bilateral middle tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 11 publications
5
57
1
5
Order By: Relevance
“…A similar study of complications of FESS in a residency training program was reported by Kinsella et al 7 in a retrospective review of 193 patients during 5 years. In this series, 21 patients developed synechiae after FESS, and patients who had undergone partial MT resection did not have a significantly increased frequency of synechia formation.…”
Section: Consupporting
confidence: 63%
“…A similar study of complications of FESS in a residency training program was reported by Kinsella et al 7 in a retrospective review of 193 patients during 5 years. In this series, 21 patients developed synechiae after FESS, and patients who had undergone partial MT resection did not have a significantly increased frequency of synechia formation.…”
Section: Consupporting
confidence: 63%
“…Minor complications such as postoperativebleedingandsynechiaeformationhavebeendocumented, with an incidence of 2% to 4%. 14 More major complications such as cerebrospinal fluid leak and visual compromise are usuallyreportedatarateoflessthan1%. 15 Postoperativecomplications due to rhinoplasty are also infrequently reported.…”
Section: Resultsmentioning
confidence: 99%
“…Two retrospective reviews from 1995 reviewed the effect of MT resection on synechiae formation between the MT and the lateral nasal wall. 1199,1200 Both found no effect.…”
Section: Xd3 Surgical Principles/techniques-mt Preservation or Resmentioning
confidence: 93%